Comparative Study of the Shear Bond Strength of Flowable Composite in Permanent Teeth Treated with Conventional Bur and Contact or Non-Contact Er:YAG Laser - Parhami, Parisa (J Lasers Med Sci, 2014)
Introduction: The aim of this study was to evaluate and compare the in vitro effect of the Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) laser with different radiation distances and high-speed rotary treatment on the shear bond strength of flowable composite to enamel of human permanent posterior teeth. Methods: freshly extracted human molar teeth with no caries or other surface defects were used in this study (n=45). The teeth were randomly divided into 3 groups. Group 1: treated with non-contact Er:YAG Laser and etched with Er:YAG laser, Group 2: treated with contact Er:YAG Laser and etched with Er:YAG laser, Group 3 (control): treated with diamond fissure bur and etched with acid phosphoric 37%. Then the adhesive was applied on the surafces of the teeth and polymerized using a curing light appliance. Resin cylinders were fabricated from flowable composite. Shear bond strength was tested at a crosshead speed of 0.5 mm/min. Results: The amount of Shear Bond Strength (SBS) in the 3 treatment groups was not the same (P<0.05).The group in which enamel surfaces were treated with diamond fissure bur and etched with acid (conrtol group) had the highest mean shear bond strength (19.92±4.76) and the group in which the enamel surfaces were treated with contact Er:YAG laser and etched with Er:YAG laser had the lowest mean shear bond strength (10.89±2.89). Mann-whitney test with adjusted P-value detected significant difference in shear bond strength between the control group and the other 2 groups (P < 0.05). Conclusion: It was concluded that both contact and non-contact Er:YAG laser treatment reduced shear bond strength of flowable resin composite to enamel in comparison with conventional treatment with high speed rotary. Different Er:YAG laser distance irradiations did not influence the shear bond strength of flowable composite to enamel.